Criteria for Publishing in Reputable International Journals: An Analytical Hierarchy Process Decision Model - Ismail Husein; Achyar Zein; Ulrich Faigle (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2025)
The problem faced by researchers, in this case lecturers at universities, after carrying out research and making research reports is deciding where to publish the results of their research. Analytic Hierarchy Process is an effective method for ranking alternative journals. This helps ensure that their research is published in a reputable journal that will reach the appropriate audience and have a positive impact on their career. The data collection method in this research was first sourced from books, the internet, and previously a study of articles and journals; secondly, create a checklist of criteria and sub-criteria from 20 (twenty) articles, namely 4 articles from Elsevier, 4 articles from Springer Nature, 4 articles from Taylor Francis, 4 articles from Wiley-Blackwell, and 4 articles from Sage. Article selection was carried out randomly. The results of distributing questionnaires were analyzed using the Analytic Hierarchy Process Online System designed by Klaus D. Goepel. The main aim of this study was to determine the appropriate weighting of several criteria that explain why previously published manuscripts are submitted to their intended publication. The criteria for accepting article manuscripts in reputable international journals using the Analytical Hierarchy Process model (standard Analytic Hierarchy Process linear scale methods) is that the first priority is the "novelty" criterion with a weight of 0.502. The second priority is the "scientific" criterion with a weight of 0.201. Furthermore, the third and fourth priorities are "manuscript" and "content" respectively with weights of 0.142 and 0.078. Meanwhile, the last priority is "Interesting" with a weight of 0.076.